Наконечники піхов мечів з Чорнівського городища ХІІІ ст. - Калініченко, Віталій; Пивоваров, Сергій; Ільків, Микола (Київ, видавець Олег Філюк, 2017)
In this article, the authors introduced into scientific circulation are rare items medieval bladed weapons that were found on the Сhornivka hillfort XIII-th century. These include three medieval «U» – these sword chapes. Given the similarities among them dating archaeological finds in Ukraine, Belarus, Poland, Romania and iconographic material (images on medieval miniatures, architectural monuments, signets) and chronology Сhornivka hillfort in general, «U» – these sword chapes refer to the middle – the second half of the XIII-th century. In addition, the author presents a detailed description of structural and morphological parameters of sword chapes. Finds ««U» – these sword chapes for scabbard Сhornivka hillfort indicate that local soldiers knew the then military chivalrous fashion and western military culture. Subjects weapons, discovered on the Сhornivka hillfort act reference as it allows to analyze the action of varioust military culture and their impact on specific territories and the general population trace their relationships and mutual influences. These findings clarify the chronological framework of Сhornivka hillfort existence and allow new position reveal its importance in the military-political development of the region’s population in the Middle Ages.
Lugs of sheathes of the swords from Сhornivka hillfort of the XIII-th century
Keywords: археологічні дослідження; Буковина; озброєння; середньовіччя; Чорнівське городище; наконечники піхов мечів; мечі; зброєзнавство; військова справа